Balancing the interests of users, publishers and developers in cases of shutdown of video games: A new European initiative - D. V. Graf (Цифровое право, 2025)
When purchasing a game, users assume that they will have ongoing unlimited access to the product—a notion that does not always correspond to reality. The nature of the relationship between publishers, developers and users as expressed in opaque licensing documentation often leaves the latter uncertain about their rights and does not guarantee them stable access to the game, which can be revoked at any time. This imbalance gives grounds to view the current regulatory framework as not entirely fair. The present study is based on statutory acts and user agreements that govern the relationship between publishers and users in cases of shutdown of gaming projects. Particular attention is paid to the analysis of the European citizens’ initiative “Stop destroying videogames,” which calls for ensuring the functionality of games even after developer support has ceased. The aim of the study is to identify concrete methods for resolving the conflict of interests between publishers, developers, and users in the event of a game closure. Through an analysis of the aforementioned initiative, an evaluation of its merits and shortcomings, and a systematic comparison with statutory acts in the fields of copyright and consumer protection, it has been determined that, despite its limited restriction of the freedom of contract and the intellectual property rights of developers and publishers, the initiative contributes to achieving an effective balance of the rights and interests of all parties. Based on the study’s findings, the author concludes that it is fair to impose a number of obligations on publishers and developers. These obligations include, for example, the removal of technical measures for copyright protection, which are implemented via connections to the developer’s servers, the permission for private server hosting, and the alteration of the game distribution model, as well as compensating users for part of their expenses in the event of the closure of games in early access.